PENGUJIAN TERMAL PENGERING GABAH UNFIXED FLATBED - I Gusti Ngurah Bagus Catrawedarma; halil halil (POLITALA PRESS, 2018)
Thermal testing of unfixed flatbed dryers was carried out on natural convection heat transfer. Its specifications are 4 number of bed level, using 1/4 Hp and 1400 rpm electric motor power and rotation, 1:60 gearbox ratio, A type of V belt with a length of 686 mm, pulleys diameter of 95 mm, and the shaft diameter of 12 mm in made sB = 70.2 kg / mm2 of the materials. Tests were carried out to determine the thermal performance of the dryer such as the amount of input energy, the energy used to evaporate the water contained in the grain, and its distribution for each level of the bed. The test results revealed that with the input energy of 6.396 kW, it took 125 minutes to evaporate the water in the rice, and the highest thermal efficiency on the 2nd level from the bottom.